Use of artificial nutrition near the end of life: Results from a French national population‐based study of hospitalized cancer patients - Karine Baumstarck; Laurent Boyer; Vanessa Pauly; Veronica Orleans; Anthony Marin; Guillaume Fond; Lucas Morin; Pascal Auquier; Sébastien Salas (Cancer Medicine)
Abstract Background The use of artificial nutrition, defined as a medical treatment that allows a non‐oral mechanical feeding, for cancer patients with limited life expectancy is deemed nonbeneficial. High‐quality evidence about the use of artificial nutrition near the end of life is lacking. This study aimed (a) to quantify the use of artificial nutrition near the end‐of‐life, and (b) to identify the factors associated with the use of artificial nutrition. Methods This was a retrospective cohort study of decedents based on data from the French national hospital database. The study population included adult cancer patients who died in hospitals in France between 2013 and 2016 and defined to be in a palliative condition. Use of artificial nutrition during the last 7 days before death was the primary endpoint. Results A total of 398 822 patients were included. The median duration of the last hospital stay was 10 (interquartile range, 4‐21) days. The artificial nutrition was used for 11 723 (2.9%) during the last 7 days before death. Being a man, younger, having digestive cancers, metastasis, comorbidities, malnutrition, absence of dementia, and palliative care use were the main factors associated to the use of artificial nutrition. Conclusion This study indicates that the use of artificial nutrition near the end of life is in keeping with current clinical guidelines. The identification of factors associated with the use of artificial nutrition, such as cancer localization, presence of comorbidities or specific symptoms, may help to better manage its use.